A putative association of COMT Val(108/158)Met with Impulsivity in binge eating disorder - Leehr, Elisabeth Johanna; Schag, Kathrin; Brückmann, Christof; Plewnia, Christian; Zipfel, Stephan; Nieratschker, Vanessa; Giel, Katrin (European eating disorders review, 2016)
Objective This study aims to investigate the influence of the COMT Val(108/158)Met polymorphism on trait and behavioural impulsivity in binge eating disorder (BED). COMT Val(108/158)Met has been related to impulsivity in previous studies, but so far no study has investigated the role of this polymorphism in the context of BED. Method Impulsivity was assessed via a questionnaire (trait) and on a behavioural level via the antisaccade task in a sample of 69 participants classified into one out of three age-matched groups: (1) obese individuals with BED according to DMS-IV (BED+); (2) obese individuals without BED, matched with the BED+ sample according to body weight (OBED-); and (3) normal-weight healthy controls (NWC). The COMT Val(108/158)Met polymorphism was genotyped in all samples. Results As expected, the BED+ sample showed higher trait and behavioural impulsivity. Furthermore, within the BED+ group, COMT Met/Met homozygous individuals showed stronger deficits in inhibitory control. Discussion COMT Met/Met homozygous individuals with BED might represent a specific group in the BED spectrum, which shows a higher behavioural impulsivity. The association between COMT Val(108/158)Met with inhibitory control should be interpreted with caution because of the small sample size. Larger replication studies are needed to further elucidate the role of the COMT Val(108/158)Met polymorphism in the regulation of disordered eating behaviour.